Green Behavior and Well-being: A Bibliometric and Network Analysis of Research Trends - Abbaszadeh Avilagh, Hamed; Pazhuhanrad, Parinaz; Eriksson-Backa, Kristina (39th Bled eConference: Co-Creating Human-Centred and Responsible Digital Futures; Conference Proceedings, 2026)
Green behavior and well-being is an interdisciplinary research domain linking environmental sustainability with mental health, happiness, and overall quality of life. Over the past three decades, it has gained substantial scholarly attention and emerged as a significant contemporary field. To examine its intellectual structure and publication trends, this study applies a bibliometric analysis of Web of Science–indexed articles. Using keyword co-occurrence analysis, six major thematic clusters were identified: nature-based public health, sustainable lifestyles, sustainable workplaces, climate perception and behavior, nature-related well-being, and subjective well-being. These clusters demonstrate that the field integrates insights from public health, environmental psychology, organizational studies, climate psychology, and happiness research, highlighting its strongly interdisciplinary nature. The results indicate that green behavior and well-being is evolving into a coherent and structured domain of inquiry. Moreover, the findings emphasize the reciprocal relationship between environmental quality and human flourishing at individual, organizational, and societal levels.